Histology and histochemistry of the testes in two Amazonian apple snails - Paschoal, Lucas Rezende Penido [UNESP]; de Oliveira, Leo Jaime Filgueira [UNESP] (My University, 2017)
This chapter describes the morphology of the testes, types of spermatozoa, and spermatogenesis in freshwater apple snails Pomacea dolioides and P. diffusa using histological and histochemical analyses. The testes and penises were fixed in 4% paraformaldehyde and processed according to the historesin routine for light microscopy. In these gastropods, the lumen of each acinus contains spermatogenic cells and mature sperm, which are distributed in a centripetal pattern surrounded by Sertoli-cells located at the acinus wall. We also observed the predominance of fusiform-shape apyrene (A) spermatozoa in the lumen of these structures, while in a lesser proportion of the eupyrene (E) wormlike-shape spermatozoa were commonly arranged near the walls of the acini. The two types of spermatozoa were intensely stained for proteins in their heads, but only the flagella of apyrene spermatozoa exhibited a strong reaction to PAS, indicating that these structures probably store glycogen. Spermatogenesis occurs in testicular acini, but no spermatozoa were registered in the penises analysed, indicating that the process of its release to the testicular acini occurs only at the final stage ofcopulation. In both species, the proportion of E/A spermatozoa was biased toward apyrenes (~1:2). The histological and histochemical patterns here recorded are similar to those observed for congeners, although the E/A spermatozoa ratio was not similar.
Keywords: Apyrene; Eupyrene; Histochemistry; Sperm morphology